The reality of the Baghdad Stock Exchange and its development prospects - Ibrahim Ahmed Jarkas (Iraqi Journal for Administrative Sciences, 2024)
The development of performance in the stock market is considered an inevitable necessity required by interacting with local and international variables and adapting to them to face the challenges imposed. This requires access to scientific and practical developments related to the mechanism of work in financial markets, benefiting from modern technologies, and striving to increase the financial tools used in trading. And diversify it to increase the investment opportunities available in the market and enhance the market's pioneering role in the national economy, despite the great development achieved by the Baghdad Stock Exchange over the past years, which is represented in mobilizing nationwide savings and directing them towards investment and contributing to increasing the savings and investment awareness among citizens, and providing the concerned market authorities with data and information about trading and the final accounts of companies and the performance of securities listed in the market and the increase in trading volume. However, many aspects require focusing on and striving to achieve. The first section dealt with the theoretical aspect of the research and its methodology; the second section was concerned with explaining the reality of the Baghdad Stock Exchange, while the third section concluded with conclusions and recommendations.